2021
DOI: 10.1186/s13256-021-02848-9
|View full text |Cite|
|
Sign up to set email alerts
|

Recurrent spontaneous abortion related to balanced translocation of chromosomes: two case reports

Abstract: Background Recurrent spontaneous abortion (RSA) is often idiopathic, but structural chromosomal abnormality is an important nosogenesis. Balanced translocations or inversions can lead to unbalanced gametes depending on the specific recombination and segregation patterns during meiosis. An unbalanced karyotype in the conceptus of a couple when one partner has a structural chromosomal abnormality may result in failure to implant, miscarriage, or ongoing pregnancy of a fetus with an unbalanced ka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 25 publications
0
9
0
1
Order By: Relevance
“…Recurrent miscarriage (RM), classically defined as two or more spontaneous miscarriages up to 20 weeks of pregnancy, is a heterogeneous disorder affecting up to 3% of couples in the reproductive period ( 1 , 2 ). American Society for Reproductive Medicine (ASRM) considers that two consecutive pregnancy losses are sufficient for diagnosing RM so far as the recurrence rate and risk factors are similar to those observed after three losses ( 1 , 3 – 6 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recurrent miscarriage (RM), classically defined as two or more spontaneous miscarriages up to 20 weeks of pregnancy, is a heterogeneous disorder affecting up to 3% of couples in the reproductive period ( 1 , 2 ). American Society for Reproductive Medicine (ASRM) considers that two consecutive pregnancy losses are sufficient for diagnosing RM so far as the recurrence rate and risk factors are similar to those observed after three losses ( 1 , 3 – 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…There are publications that HLA complex suppresses maternal immune response required for implantation and in the presence of homogeneous histocompatibility complex (common for the mother and father) in inbred populations, the frequency of RM increases ( 20 ). The choice of polymorphisms of CTLA4 (rs-3087243, CT60 G/A) and CX3CR1 (rs3732379, Val249Ile) and genes of HLA DQA1, DQB1, and DRB1 (class II major histocompatibility complex) for the analysis of immune processes in iRM is statistically determined by their participation in T-cell tolerance and suppression of significant associations with RM according to GWAS data ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following publication of the original article [ 1 ], the authors identified an error in the affiliations 1–3.…”
Section: Correction To: J Med Case Rep (2021) 15: 270 Https://doiorg/101186/s13256-021-02848-9mentioning
confidence: 99%
“…The affiliations have been updated in the correction article and the original article [ 1 ] has been corrected.…”
Section: Correction To: J Med Case Rep (2021) 15: 270 Https://doiorg/101186/s13256-021-02848-9mentioning
confidence: 99%